NFC based attendance: More than just a touch - Zuhedy Zay, Aqqiela Zuhra; Mohd. Nor, Rizal; Mohamed Razi, Mohamed Jalaldeen; Mantoro, Teddy; Anugerah Ayu, Media (Penerbit UTM Press, 2016)
The use of NFC technology is growing rapidly and implemented in various applications. It aims to reduce the steps needed to perform tasks by the user in day to day operations such as payment, electronic ticketing, attendance system, and other office related tasks. In this study, university smart environment is implemented using NFC for attendance monitoring system to reduce the need of tedious tasks. The application involves several different concerns in access control and managing physical and virtual components. These concerns are studied to create an easy-used attendance monitoring system using NFC to be applied in a smart university environment. A survey is conducted to measure students and lecturers acceptance in using NFC as an attendance monitoring system. The results provide insights on students and lecturers acceptance in using this technology. Additionally, it shows that both students and lecturers agree on the NFC attendance system should be implemented to ease attendance monitoring in the university.